Keterbacaan Teks pada Buku Bahasa Indonesia SMA Kelas XI Kurikulum Merdeka menggunakan Grafik Fry - Dewi Tri Handayani; Ayu Wulandari; Muhammad Nur Hanif (Repetisi: Riset Pendidikan Bahasa dan Sastra Indonesia, 2026)
The research on the Readability of Texts in Indonesian Language Textbooks for Grade XI of Independent Curriculum using Fry Graphs was motivated by the findings of the phenomenon of the use of discourse that is not appropriate for its class, thus affecting students' learning motivation. This study examines the level of readability of Indonesian Language textbooks for Grade XI of Independent Curriculum using Fry Graphs. This study aims to find the level of readability of Indonesian Language textbooks for Grade XI of Independent Curriculum measured using the Fry Graph formula. This study uses a qualitative descriptive approach. Data sources were obtained from discourses in Indonesian Language textbooks for Grade XI of Independent Curriculum. The methods and techniques of data collection in this study were the listening method and note-taking technique, while the methods and techniques of data analysis in this study used the Miles and Huberman model. The results of the analysis found that the Indonesian Language textbook for Grade XI of Independent Curriculum had a high level of readability, seen from the fifteen data analyzed for readability using Fry Graphs, there were nine discourses that were appropriate for grade XI and there were six discourses that were not appropriate for grade XI. The nine discourses are entitled Why They Pray to Trees, Barbers, Homeland, Angels Also Know, Mangir Drama, A Bowl of Farewell on the Dining Table, Wayang Potehi: Faded Love, Status of Coral Reef Conditions in Ambon Bay and Maleo Senkawor. Based on the results of the data analysis, it can be concluded that the Indonesian Language textbook for Senior High School Grade XI Merdeka Curriculum has a readability level that is in accordance with grade XI because the meeting point between the number of sentences from the perpendicular line and the number of syllables from the horizontal line falls in the grade XI level area. This research is expected to be a reference and consideration for further research.